2015
DOI: 10.1038/srep18553
|View full text |Cite
|
Sign up to set email alerts
|

Association of telomere length and mitochondrial DNA copy number with risperidone treatment response in first-episode antipsychotic-naïve schizophrenia

Abstract: Accumulating evidence indicates a putative association of telomere length and mitochondrial function with antipsychotics response in schizophrenia (SCZ). However, pharmacological findings were limited and no previous work has assessed this in a prospective longitudinal study. This study assessed telomere length and mitochondrial DNA copy number in first-episode antipsychotic-naïve SCZ patients with 8-week risperidone treatment to evaluate the association between these biomarkers and clinical treatment response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 46 publications
2
51
1
2
Order By: Relevance
“…However, one large study reported longer LTL in schizophrenia than in HCs (Nieratschker et al, 2013). Yet other studies have detected no difference in LTL between individuals with schizophrenia and HCs (Li et al, 2015;Malaspina et al, 2014;Mansour et al, 2011). Reasons for discrepancies in findings among these studies are not known, but may include inadequate sample sizes, differing gender distributions, quality of diagnostic evaluations, nature of the comparison sample, chronicity and severity of illness, medical illnesses, medication history, and history of treatment responsiveness, along with demographic and lifestyle factors such as age, diet, body-mass index (BMI), exercise, and tobacco use.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, one large study reported longer LTL in schizophrenia than in HCs (Nieratschker et al, 2013). Yet other studies have detected no difference in LTL between individuals with schizophrenia and HCs (Li et al, 2015;Malaspina et al, 2014;Mansour et al, 2011). Reasons for discrepancies in findings among these studies are not known, but may include inadequate sample sizes, differing gender distributions, quality of diagnostic evaluations, nature of the comparison sample, chronicity and severity of illness, medical illnesses, medication history, and history of treatment responsiveness, along with demographic and lifestyle factors such as age, diet, body-mass index (BMI), exercise, and tobacco use.…”
Section: Introductionmentioning
confidence: 77%
“…Thus far, cross-sectional studies have reported mixed results. Several investigations found shorter LTL in persons with schizophrenia than in healthy comparison subjects (HCs) (Fernandez-Egea et al, 2009;Kao et al, 2008) or at least in subgroups of individuals with more chronic, severely psychotic, or treatment-resistant illness (Kota et al, 2015;Li et al, 2015;Rao et al, 2016;Yu et al, 2008) (but see (Lin, 2015)), possibly suggesting accelerated biological aging Kirkpatrick et al, 2008). However, one large study reported longer LTL in schizophrenia than in HCs (Nieratschker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have investigated the association between LTL and psychopharmacological outcomes. To date, only three studies (one in bipolar disorder and two in schizophrenia) have examined the relationship between LTL and treatment response to psychiatric medications [1820], two of which assessed clinical treatment outcomes retrospectively [18, 19]. Martinsson et al [18] retrospectively assessed lithium response in 121 patients with bipolar disorder and found that lithium non-responders had significantly shorter LTL than responders.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [19] retrospectively assessed clinical response to antipsychotics in a group of 68 inpatients with schizophrenia, and found that poorer treatment response was associated with shorter LTL. Li et al [20] assessed telomere length in 89 first-episode, antipsychotic-naïve patients with schizophrenia prior to beginning eight weeks of open-label risperidone treatment, and found that poorer treatment response (<50% symptom improvement after treatment) had shorter LTL. Additionally, a placebo-controlled study by Rasgon et al [21] examined LTL as a predictor of antidepressant response to the addition of Pioglitazone (a peroxisome proliferator-activated receptor [PPAR-γ] agonist) in 42 patients with unremitted MDD who were already attempting to treat their depression with another medication(s).…”
Section: Introductionmentioning
confidence: 99%
“…In peripheral samples such as blood, mtDNA copy number has been observed to be decreased in first-episode neuroleptic-naïve subjects with SZ [19]. In addition, differences in copy number were observed between risperidone responders and nonresponders, i.e.…”
Section: Introductionmentioning
confidence: 99%